Top incomes in Sweden over the twentieth century - Jesper Roine; Daniel Waldenström (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
This paper presents homogenous series of top income shares in Sweden from 1903 to 2003 using individual tax returns data. We find that Swedish top incomes have developed more similarly to the US, Canada and the UK than to other continental European countries when capital gains are included. The top income shares are U-shaped over time, falling steadily until around 1980 when they start increasing again. Around 2000 they reach levels similar to those found around 1950, before the expansion of the Swedish welfare state. However, unlike the Anglo-Saxon countries, where the recent increases were mainly driven by increased wage earnings inequality, Swedish top income shares have risen almost exclusively due to capital gains, a finding consistent with relatively high marginal wage taxes and internationally high price increases in financial and real estate markets since 1980. When excluding capital gains the increase in top income shares since 1980 almost disappears and the Swedish experience looks more like that of continental Europe. Furthermore, we also find that the largest decrease of top income shares happens between 1935 and the beginning of the 1950s, but not (as in the US and in France) during the war years, but before 1939 and after 1945 suggesting that the Swedish development was more driven by policy than by exogenous shocks.
Keywords: D31; H20; J30; N30; 330; Income inequality; Top incomes; Sweden; Taxation; Einkommensverteilung; Schätzung; Schweden